Problem-based learning and problem solving model: which is more effective in improving student learning achievement? - Jonás Solissa; Jusuf Blegur; Zuvyati Aryani Tlonaen (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Identifying the syntax of student learning experiences in learning models helps lecturers be more selective in determining the relevance of learning models and student learning achievements that lecturers have previously formulated. This research aims to determine the increase in student learning achievement, using the problem-based learning (PBL) learning model and the problem-solving (PS) learning model, testing the differences in the application of the PBL and PS models on student learning achievement, and finding out which learning model is more effective in improving Student learning outcomes in sports sociology courses. This research is a quasi-experimental research with a pre-test-post-test non-equivalent comparison-group design. The research sample consisted of 60 students (30 PBL and 30 PS groups) taking sports sociology courses. The research instrument includes ten learning achievement essay test questions developed from critical thinking indicators. The data was analyzed descriptively, testing differences using the independent sample t-test and N-Gain analysis to see the effectiveness of the PBL and PS models on student learning achievements. The research results prove an increase in learning achievement for both groups using PBL and PS. Meanwhile, from the results of statistical tests, there are significant differences in learning achievement between the PBL and PS groups. Furthermore, from the results of the N-Gain test, it turns out that PBL is more effective in improving student learning achievement than the PS model.